2022
DOI: 10.3390/ijerph19137573
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impacts of Preventative Health Behaviors with Respect to COVID-19: An Altruistic Perspective

Abstract: This study aims to explore the impact of gender and anxiety on various preventative health behaviors, and the relationships among these preventative health behaviors, individual well-being and depression, from the perspective of altruism. This study employed an online questionnaire survey, and 136 males and 204 females participated in the survey. The results of this study showed that females exhibited better preventative health behaviors than males, including hygiene habits, social distancing and behaviors int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…A possible explanation for the limitation to teachers’ self-protection reasons for wearing a mask (both one’s wearing and expecting others to wear a mask) is provided by the literature on motives for health behaviors showing that “anxiety encourages individuals to seek safety-promoting behaviors to protect themselves” ([ 47 ] p. 3; [ 48 ]), but can promote altruism when the outcome of a specific self-protecting behavior has a beneficial impact on future interactions with individuals profiting from these actions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for the limitation to teachers’ self-protection reasons for wearing a mask (both one’s wearing and expecting others to wear a mask) is provided by the literature on motives for health behaviors showing that “anxiety encourages individuals to seek safety-promoting behaviors to protect themselves” ([ 47 ] p. 3; [ 48 ]), but can promote altruism when the outcome of a specific self-protecting behavior has a beneficial impact on future interactions with individuals profiting from these actions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the public gainframed message was not associated with any outcome variable. This message was intended to appeal to people's altruism because several studies have indicated that altruistic motivation may promote healthy behaviors [34][35][36]. However, with regard to social participation, altruism could not be a motivation.…”
Section: Discussionmentioning
confidence: 99%